2004
DOI: 10.1103/physreve.70.011505
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory behavior of nanodroplets

Abstract: Molecular dynamics (MD) simulations were performed in order to investigate the phenomenon of free oscillations of nanodroplets and the extent to which the continuum theory for such oscillations holds at nanoscales. The effect of temperature on these oscillations is also studied. The surface tension, a key property for the phenomenon of interest, was evaluated and compared with the experimental values of argon, showing that with an appropriate choice of the cutoff distance in the MD simulations, it is possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…The intrinsic width obtained in the MDS of monatomic LJ model fluids (when the model LJ interaction potential of the particles was very close to that measured experimentally, for example between argon atoms) was found to be in very good agreement with that estimated from experiments. 21,[23][24][25] Similar values of the intrinsic width were reported for the liquid-gas interfaces of carbon tetrachloride, water, alkanes and alcohols. 25 Therefore, it is difficult at the moment to expect, at least for simple interfaces, that the relaxation times of the surface phase would be on the time scale required by the IFT.…”
Section: Introductionsupporting
confidence: 74%
“…The intrinsic width obtained in the MDS of monatomic LJ model fluids (when the model LJ interaction potential of the particles was very close to that measured experimentally, for example between argon atoms) was found to be in very good agreement with that estimated from experiments. 21,[23][24][25] Similar values of the intrinsic width were reported for the liquid-gas interfaces of carbon tetrachloride, water, alkanes and alcohols. 25 Therefore, it is difficult at the moment to expect, at least for simple interfaces, that the relaxation times of the surface phase would be on the time scale required by the IFT.…”
Section: Introductionsupporting
confidence: 74%
“…This effect of the capillary wave motion has been clearly observed and studied in MD simulations and in the experiments on simple fluids [8,36,48,49,[51][52][53][54][55]. In particular, MD simulations of nanoscale capillary waves (with amplitude ≈ 0.3 particle diameters) in liquid argon drops have decisively demonstrated that capillary wave motion closely follows predictions of continuum hydrodynamics (frequency and damping coefficient), the observed temperature dependence of the density profile width is in a very good agreement with experiments on liquid argon [51,52]. The width of the density profile was found to be within 1.…”
Section: A the Density Profile In Monatomic Lj Liquid Dropsmentioning
confidence: 81%
“…[53,55,62,78]) for drops of up to ∼ 8 × 10 5 LJ particles corresponding to radii of almost 100 diameters [62]. It is also very clear that the fluid drops experience large fluctuations in shape and size, particularly in the case of large systems, as has been shown by Arcidiacono et al [61] and Salonen et al [64]. With a thermodynamic approach based on a linear response of the free energy to small volume perturbations, El Bardouni et al [55] reported some values of the tension for spherical and cylindrical surfaces that are larger than the planar limit (corresponding to δ < 0), though the uncertainty is such that they concluded that the tension is essentially curvature independent.…”
Section: Introductionmentioning
confidence: 75%